Biocompatible porous boron nitride nano/microrods with ultrafast selective adsorption for dyes. Issue 1 (February 2021) - Zhao, Zhao; Bai, Changning; An, Lulu; Zhang, Xiaofang; Wang, Fan; Huang, Yin; Qu, Mengnan; Yu, Yuanlie
Graphical abstract: Highlights: Porous boron nitride (BN) nano/microrods with high surface area, large pore volume and small pore size are fabricated.. These BN nano/microrods show ultrafast adsorption rate for methylene blue. These porous BN nano/microrods exhibit rapid and efficient selectivity for cationic dyes in the mixtures containing anionic and cationic dyes. These porous BN nano/microrods have good biocompatibility that can be used as promising candidates for wastewater treatment. Abstract: Wastewater treatment and separation technologies are critical to meet global challenges of insufficient water supply and inadequate resources. However, simple adsorption can no longer satisfy these demands, and thus more and more water recovery technologies have attracted attention. Here, we report a novel kind of porous BN nano/microrods with excellent features including high surface area of 1109.11 m²/g, large pore volume of 0.454 cm³/g and small pore size of 2.60 nm. These unique properties make the as-obtained porous BN nano/microrods show an ultrafast adsorption rate for the cationic dye methylene blue (MB + ), and they can also be able to selectively adsorb cationic dyes from the mixtures of anionic and cationic dyes. The corresponding selective adsorption mechanism is also proposed based on the microstructure and surface property of the as-obtained porous BN nano/microrods. Furthermore, the cytotoxicity test was performed and the results show that the as-obtained porous BN nano/microrods have good biocompatibility with the cell survival rate of 80 % after a test period of 5 days, and this result is much higher than that of commercial BN. This finding provides a new application field for BN nanomaterials to selectively adsorb/separate anionic and cationic dyes in organic dye-containing wastewater treatment.